Politique énergétique 2030 du Québec : l’étonnante absence d'une stratégie de transport soutenable - Évariste Feurtey; Louis-Étienne Boudreault; Gilles Bourque; Simon-Philippe Breton; Réal Reid; Carol Saucier; Bernard Saulnier; Lucie Sauvé (VertigO)
Following a text published in « Le Soleil » on April 7th entitled "The Forced Future of Wind Energy in Québec" (Saucier et al., 2016), a collective of eight researchers, members of the Collectif scientifique sur la question du gaz de schiste, question the ambition and the strategic orientations of Québec's energy policy (QEP) 2030 for the transportation sector. Current forecasts show major annual electricity surpluses until 2023 in Québec (8,3 TWh/yr), a volume that represents more than what is needed to fully substitute the annual fossil fuel consumed by car transportation today. Yet, despite the ambitious objectives of QEP 2030, there appears to be no documented action plan describing the structured deployment required to get there. Why is it that Québec has not yet been able to develop a responsible, ambitious and imaginative electricity substitution roadmap for the transportation sector like the one adopted 50 years ago when the deployment of the hydroelectricity infrastructure became the main strategic focus of a modern Quebec economy ? This is the fundamental question raised in this article.